2023
DOI: 10.3390/nu15040941
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Beta-Amyloid-Activated Primary Human Neutrophils by Dietary Phenols from Virgin Olive Oil

Abstract: The defense mechanism against harmful stimuli is inflammation. Indeed, neurodegenerative disorders can arise as a result of a persistent neuroinflammation. Beta-amyloid (Aβ1-42) is an early trigger in the origination of Alzheimer’s disease, leading to synaptic and cognitive impairments. Virgin olive oil (VOO) is correlated with a decreased risk of developing immune-inflammatory disorders, but the potential effects of the phenolic fraction (PF) from VOO in the modulation of neuroinflammatory processes in neutro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Epidemiological studies reviewed have revealed an inversely proportional relationship between the consumption of phenol-rich foods, such as tea, coffee, wine, chocolate, and fruits, and the risk of developing Alzheimer's disease (Pintać et al, 2022;Rivero-Pino et al, 2023). These results support the hypothesis that phenols may prevent or delay the onset of this disease by protecting neurons from oxidative stress and inflammation, two critical pathogenic factors in Alzheimer's disease (Cherbuin et al, 2022;Juiz & Lenarz, 2023).…”
Section: The Impact Of Chemical-computational Tools On Drug Discoverymentioning
confidence: 63%
See 1 more Smart Citation
“…Epidemiological studies reviewed have revealed an inversely proportional relationship between the consumption of phenol-rich foods, such as tea, coffee, wine, chocolate, and fruits, and the risk of developing Alzheimer's disease (Pintać et al, 2022;Rivero-Pino et al, 2023). These results support the hypothesis that phenols may prevent or delay the onset of this disease by protecting neurons from oxidative stress and inflammation, two critical pathogenic factors in Alzheimer's disease (Cherbuin et al, 2022;Juiz & Lenarz, 2023).…”
Section: The Impact Of Chemical-computational Tools On Drug Discoverymentioning
confidence: 63%
“…There are strategies designed for healthy mental aging (Yamada et al, 2015;Shahidi & Yeo, 2018), highlighting the adoption of healthy habits and incorporation of social, physical and cognitive activities (Makrakis et al, 2022), which, in conjunction with an anti-inflammatory diet high in phenols, can lead to a lower incidence of AD (Tobias et al, 2014;Gao et al, 2019;Bermejo-Pareja et al, 2016;Fernandez et al, 2018.;Azar et al, 2021;Chu et al, 2023). Some phenol-rich foods, such as olive oil, red wine, coffee, tea, cocoa-derived products, a variety of fruits, culinary herbs, and vegetables, have been identified as important sources of polyphenols (Angeloni et al, 2017;Holland et al, 2020;Pintać et al, 2022;Rivero-Pino et al, 2023).…”
Section: Epidemiological Studiesmentioning
confidence: 99%
“…Consequently, this feature has been the subject of many in vitro studies studying the neuroprotective activities of EVOO phenolic compounds (Table 2). Thus, the accumulation of protein aggregates was simulated by treating SH-SY5Y cells [35,42] and neutrophils [40] with Aβ1-42 oligomers to reproduce conditions similar to those encountered in Alzheimer's disease (AD). In SH-SY5Y, HT in synergy with oleuropein, activated the autophagic flux in order to prevent cell damage by Aβ1-42 oligomers, while HT alone (0-20 µM) accelerated the formation of harmless fibrils to the detriment of harmful ones.…”
Section: Neurodegeneration Modelsmentioning
confidence: 99%